The changing demand for qualified labour in New Zealand - Ralph Lattimore; Gary Hawke; Ian Duncan; John Ballingall (New Zealand Institute of Economic Research (NZIER), 2002)
The relative decline in unskilled wages worldwide has prompted some commentators to place the blame on globalisation and trade liberalisation. A more likely cause in the New Zealand context is technical change that favours the employment of skilled labour. This hypothesis is tested using shift share and factor content analysis for 1986, 1996 and 2001. The results suggest that the upskilling that has occurred economy wide has dominated the effects of any reallocation of highly skilled workers between sectors that may have been caused by trade liberalisation in New Zealand. The upskilling has occurred in the form of rapidly increasing numbers of employees with bachelors and higher degrees. This effect combined with a very large reduction over the last five years in employee numbers with sub degree qualifications raises questions about the prevalence of `sheepskin' effects and supply induced demand in the education sector.
Keywords: F1; J4; O3; 330; Trade; Labour Markets; Technological Change; Arbeitsnachfrage; Facharbeiter; Neuseeland